PISA Vocational Education and Training (VET) : assessment and analytical framework - (:unkn) unknown (OECD, 2024)
„This report presents the conceptual foundations of the OECD Programme for International Student Assessment (PISA) Vocational Education and Training (VET), currently in the Development Phase of implementation which aims to provide a comprehensive and rigorous international survey of student knowledge and skills that are essential for success in selected occupational areas. The PISA-VET assessment covers professional knowledge and skills in five occupational areas (automotive technician, business and administration, electrician, nursing/healthcare assistant and hotel receptionist), plus an evaluation of learners’ employability skills, including literacy, problem solving, task performance (conscientiousness) and collaboration with others. This publication includes the frameworks for assessing all the knowledge and skills included in the assessment. These chapters outline the content knowledge and skills that learners need to acquire in each domain, how each domain is assessed, and the contexts in which this knowledge and these skills are applied. The publication also presents the frameworks for the various questionnaires distributed to students, principals of VET institutions, teachers and trainers, including a questionnaire for trainers in work-based learning environments and a system level data questionnaire for participating countries. The questionnaires are also included as an annex to the publication.“ (editor; BIBB-Doku)

Die OECD entwickelt derzeit eine internationale Kompetenzmessung in der Berufsbildung (kurz PISA VET) nach Vorbild des bekannten „Programme for International Student Assessment“ (kurz PISA). Geplant ist die Messung von beruflichen Kompetenzen in fünf Berufsfeldern: Elektroniker*in, Kfz-Mechatroniker*in, Kaufmännisch-verwaltende Berufe, Gesundheitsberufe, und Tourismus und Gastgewerbe. Hierbei wurden in Expertengruppen unter anderem berufstypische Arbeitsaufgaben und Tätigkeiten und Leitlinien definiert, um in Folge entsprechende Testinstrumente entwickeln zu können. (BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S 2.2.5 Standards in der beruflichen Bildung; L 6.3.1 Diagnose- & Messinstrumente; S 6.4.7.1 Gästebetreuer; 370; Berufsbildungs-PISA; Kompetenzfeststellung; Elektroniker; Kraftfahrzeugmechatroniker; Verwaltungsberuf; Kaufmännischer Beruf; Gesundheitsberuf; Fremdenverkehrsberuf; Hotelfachmann; Tätigkeitsanalyse; Tätigkeitsmerkmal; Kompetenzprofil; ASCOT Forschungs- und Transferinitiative; Internationaler Vergleich